SISTEM AKUNTANSI PENJUALAN DENGAN METODE CASH AND CARRY PADA PT RANUM GOWA - andi asirah (VALUE, 2021)
This study aims to determine the sales accounting system with the cash and carry method at PT.Ranum. The effective sale of a product by the company is a determinant in the company's activities. These conditions motivate companies to apply cash sales accounting systems to get good income. This research was carried out with a descriptive method. The types of data used are primary data and secondary data. Data collection techniques using interview techniques and observation techniques. The results obtained, the sales cycle applied by most companies is appropriate and effective because it is in accordance with the theory so that it can support control in sales